Atkinson, Sarah; Fuller, Sara; Painter, Joe (eds.) (2012). Wellbeing and place - Ortiz Guitart, Anna (Documents d'Anàlisi Geogràfica, 2013)
Atkinson, Sarah; Fuller, Sara; Painter, Joe (eds.) (2012) Wellbeing and place Surrey: Ashgate, 254 p. ISBN 978-1-4094-2060-6